Land capability analysis using computerised overlay techniques - Hammond, C. M. (My University, 2015)
A versatile computerised overlay technique to analyse relatively constant, objectively measured, land characteristics for their capability to sustain any defined land use was developed. The mapped form of each land characteristic, be it of a polygonal, network or discrete point distribution is stored in a data base system for subsequent retrieval and overlay by a grid of selected cell size. The capability rating of each measured land characteristic value is derived from a capability graph or table which relates this value to a capability scale according to existing information. A foreclosure of options in land use is also performed. The influence of each characteristic upon the overall capability for a defined land use is included by user defined weighting values. The overall capability of an overlaid grid cell is the weighted mean of the individual capability values for each land characteristic analysed. The result is mapped by overprinting on a line printer. Information to select the land characteristics analysed for a land use, to develop the capability graphs and tables, to quantitatively analyse interrelationships between land characteristics and to define weighting values was gathered from the literature and various people. This information which controlled the analysis of the land for a land use and default sets of weighting values used if the user makes no choice, are stored in the data base system. The capability analysis program is composed of a suite of interactive and non-interactive FORTRAN programs. A trial run of the procedure was compared with a ranual land capability analysis for an agricultural land use in Northern Lebowa, South Africa. The results illustrated the influence on tfo overall capability of both the weighting value and the selected overlay grid cell size. The value of a versatile capability analysis tool which can analyse any defined land use, using selected weighting values and grid cell sizes, was seen. The procedure is also not restricted by the study area size, the scale at which the land is surveyed, the choice of land characteristics used in the analysis, the shape of the capability graphs and the values contained in the capability tables.